2005
DOI: 10.1063/1.1857465
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronically automated system for carbon nanotubes synthesis via arc-discharge in solution

Abstract: The method of arc discharge in the solution is unique and inexpensive route for synthesis of the carbon nanotubes ͑CNTs͒, carbon onions, and other carbon nanostructures. Such a method can be used for in situ synthesis of CNTs decorated with nanoparticles. Herein, we report a simple and inexpensive optoelectronically automated system for arc discharge in solution synthesis of CNTs. The optoelectronic system maintains a constant gap between the two electrodes allowing a continuous synthesis of the carbon nanostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Recently, the synthesis of carbon nanotubes in the solution plasma has been the subject of vigorous investigation [3][4][5][6][7]. Nomura et al demonstrated the synthesis of carbon-related materials with a microwave-generated plasma in a hydrocarbon liquid under evacuation [6].…”
Section: Nanoparticle Synthesis By Solution Plasma Processingmentioning
confidence: 99%
“…Recently, the synthesis of carbon nanotubes in the solution plasma has been the subject of vigorous investigation [3][4][5][6][7]. Nomura et al demonstrated the synthesis of carbon-related materials with a microwave-generated plasma in a hydrocarbon liquid under evacuation [6].…”
Section: Nanoparticle Synthesis By Solution Plasma Processingmentioning
confidence: 99%
“…Recently, arc-discharge methods in the liquid phase have attracted considerable attention [2][3][4][5][6][7][8][9][10][11][12][13][14] due to their low cost and simple instrumentation to synthesize carbon nanotubes. In our previous communications [11,12,14], the arc discharge in solution (ADS) procedure is discussed elaborately. In 2000, Ishigami et al [2] first reported the continuous synthesis of MWCNTs in liquid nitrogen using a dc power supply of 20-25 V operating at 60 A. Hsin and co-workers [3] attempted to produce metal-filled CNTs using arc discharge in a cobalt sulfate solution, which resulted in the formation of CNTs filled with not only metallic cobalt but also cobalt sulfide particles.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, TEM analysis confirmed the hollow structure of CNTs. The graphene layers which constituted the wall of the nanotubes were not so straight [11]. This greater disorder between carbon planes was assigned to the relatively low temperature catalytic growth process.…”
Section: Resultsmentioning
confidence: 99%